2002
DOI: 10.1046/j.1365-2141.2002.03254.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro expansion of cord blood does not prevent engraftment of severe combined immunodeficient repopulating cells

Abstract: Summary. This study aimed to assess the potential of human cord blood (CB) cells to engraft in the xenogenic non-obese diabetic/severe combined immunode®cient (NOD/SCID) mouse model after in vitro expansion culture. We also studied the quality of human haemopoiesis arising from the transplantation of fresh or expanded cells in this model. Cord blood CD34 + cells were cultured for 3, 7 or 10 d with stem cell factor, Flt3, thrombopoietin, interleukin 3 (IL-3), IL-6 and granulocyte colony-stimulating factor, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Cord blood or bone marrow mononuclear cells (MNC) were prepared from 40–50 ml of CB or 5 ml bone marrow using lymphoprep ( d = 1·077 g/ml, Nycomed, Birmingham, UK) density gradient separation followed by treatment with ammonium chloride lysing solution for 15 min at 4°C to remove red cells. CD34 + cells were prepared as previously described (Denning‐Kendall et al , 2002) using the immunomagnetic MiniMACS column system with the CD34 + stem cell isolation kit (Miltenyi Biotec, Bisley, UK) as specified by the manufacturer. These preparations contained >80% CD34 + cells by flow cytometry analysis.…”
Section: Purification Of Cd34+ Cells From Cord Blood and Bone Marrowmentioning
confidence: 99%
See 1 more Smart Citation
“…Cord blood or bone marrow mononuclear cells (MNC) were prepared from 40–50 ml of CB or 5 ml bone marrow using lymphoprep ( d = 1·077 g/ml, Nycomed, Birmingham, UK) density gradient separation followed by treatment with ammonium chloride lysing solution for 15 min at 4°C to remove red cells. CD34 + cells were prepared as previously described (Denning‐Kendall et al , 2002) using the immunomagnetic MiniMACS column system with the CD34 + stem cell isolation kit (Miltenyi Biotec, Bisley, UK) as specified by the manufacturer. These preparations contained >80% CD34 + cells by flow cytometry analysis.…”
Section: Purification Of Cd34+ Cells From Cord Blood and Bone Marrowmentioning
confidence: 99%
“…Siglec-5 is upregulated later than CD33 during in vitro differentiation of CD34 + cells To further investigate when Siglec-5 might be switched on during myelopoiesis, CB purified CD34 + cells were cultured with a combination of cytokines (SCF, IL-3, IL-6, G-CSF, Flt-3 and TPO) previously shown to induce both expansion and maturation of myeloid progenitors from CD34 + stem cells (Denning-Kendall et al, 2002).…”
Section: Siglec-5 Is Not Expressed On Cd34 + Progenitor Cellsmentioning
confidence: 99%
“…In this way, we obtained unequivocal proof that SRC activity was enhanced after the ex vivo expansion culture. To quantify these data, we performed a limiting dilution assay 31 on the CD34 + CXCR low CD133 + population at the beginning and after culture (see further text for the CD133 issue), the results of which showed an ~4.2-fold expansion of SRCs after 7 days with respect to day 0 ( Figure 3A-C ). Furthermore, the mean individual SRC proliferative capacity was ~4-fold higher after 7 days of expansion culture compared to the capacity at day 0 ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Ex vivo expansion of human UCB stem and progenitor cells becomes a critical issue in UCB clinical transplantation and immunotherapy. A small number of groups reported that certain combination of cytokines could preserve the activity of transplanted cells [13,22,23]. Guenechea et al [7] found that these cells retained their capacity to support long-term repopulation with delayed engraftment as compared to fresh cells, whereas Piacibello et al [24] reported that CD34 + CB cells, expanded for up to 10 weeks, maintained their in vivo repopulating potential.…”
Section: Discussionmentioning
confidence: 98%